Intesification of tower gas washer in the soda ash production - Моісєєв, Віктор Федорович; Манойло, Євгенія Володимирівна; Грубнік, Аліна Олегівна (Technology audit and production reserves, 2015)
The results of studies on the effectiveness of existing designs of soda production absorbers for purification of gas emissions from ammonia are given. The main sources of ammonia emissions from the production of soda ash production are defined and shortcomings of existing equipment are shown. Protection of air from pollution by industrial emissions is one of the most important issues of our time that covers in one way or another almost all countries of the world, regardless of their level of industrial development. It does not recognize territorial borders. Therefore, the creation of new designs of machines for cleaning, improvement of the existing gas purification equipment is the only way to increase the volume of economic activity and the expansion of production. Based on the analysis of design and the performance of the absorption apparatus it is proved expediency of creating a new structure of the vortex unit, which will increase the degree of purification, reduce the production area, which occupies the dust removal equipment, and reduce the energy costs of the cleaning process. The authors have developed a new design of the vortex absorber and materials are sent at obtaining a patent of Ukraine.